Comparison of Femtosecond Laser-Enabled Descemetorhexis and Manual Descemetorhexis in Descemet Membrane Endothelial Keratoplasty. Issue 7 (July 2017) - Einan-Lifshitz, Adi; Sorkin, Nir; Boutin, Tanguy; Showail, Mahmood; Borovik, Armand; Alobthani, Murad; Chan, Clara C.; Rootman, David S.
Abstract : Purpose: To introduce a novel method to perform descemetorhexis in Descemet membrane endothelial keratoplasty (DMEK) using the femtosecond laser and to compare it with Descemet membrane endothelial keratoplasty performed with manual descemetorhexis (M-DMEK). Methods: A retrospective medical chart review of 2 groups of patients who underwent DMEK surgery combined with cataract surgery secondary to Fuchs corneal endothelial dystrophy and cataract: 17 patients underwent femtosecond laser-enabled descemetorhexis Descemet membrane endothelial keratoplasty (FE-DMEK) and 89 patients underwent DMEK surgery with M-DMEK. Best spectacle-corrected visual acuity, endothelial cell density (ECD), graft detachment rate, and complications were compared. Results: Average age of the 106 patients (64 women and 42 men) was 68 ± 11 years. Postoperative best spectacle-corrected visual acuity was 0.19 ± 0.13 logarithm of the minimum angle of resolution in the FE-DMEK group and 0.35 ± 0.48 logarithm of the minimum angle of resolution in the M-DMEK group ( P = 0.218). One day after surgery, there were no significant graft detachments in the FE-DMEK group, compared with 20% graft detachment rate in the M-DMEK group ( P = 0.041). Rebubbling was performed in 17% of eyes in the M-DMEK group compared with none in the FE-DMEK group ( P = 0.066). The mean endothelial cell count in the FE-DMEK and M-DMEK groups at 6 months after surgery were 2105 ± 285 cells per square millimeter (24% cells loss) and 1990 ± 600 cells per square millimeter (29% cells loss), respectively ( P = 0.579). Conclusions: FE-DMEK shows efficacy similar to that of M-DMEK with apparently less graft detachment and reduced need for rebubbling.